ANALYSIS OF STUDENT SATISFACTION IN ANALYTICAL CHEMISTRY COURSE - Maria Aloisia Uron Leba; Maria Benedikta Tukan; Faderina Komisia (Universitas Negeri Surabaya, 2020)
The purpose of this research to 1). know the level of student satisfaction, 2). Know the achievement of lecturer performance, 3).study the best performance of lecturers, 4). Study the aspects that need to be improved in lectures. The sample of this research was the 3rd semester students of the Chemistry Education Study Program of Unika Widya Mandira who programed analytical chemistry I. The technique of data collection used was a questionnaire. This data was analyzed descriptively quantitative. Based on the results of data analysis, 58.6% of students said they were very satisfied and 41.4% said they were satisfied with the lecturers' performance. The achievement of lecturers' performance is included in the excellent category with an average of 87%. There are eight aspects that become the best performance and five aspects that need to be improved in further lectures.